Evaluation of ferritin and TfR level in plasma neural-derived exosomes as potential markers of Parkinson’s disease - Chen, Zhi-ting; Pan, Chu-zhui; Ruan, Xing-lin; Lei, Li-ping; Lin, Sheng-mei; Wang, Yin-zhou; Zhao, Zhen-Hua (Frontiers in Aging Neuroscience, 2023)
Early diagnosis of Parkinson's disease (PD) remains challenging. It has been suggested that abnormal brain iron metabolism leads to excessive iron accumulation in PD, although the mechanism of iron deposition is not yet fully understood. Ferritin and transferrin receptor (TfR) are involved in iron metabolism, and the exosome pathway is one mechanism by which ferritin is transported and regulated. While the blood of healthy animals contains a plentiful supply of TfR-positive exosomes, no studies have examined ferritin and TfR in plasma neural-derived exosomes. This study aimed to investigate the mechanism of iron deposition and identify novel biomarkers for PD by measuring of ferritin and TfR levels in plasma neuralderived exosomes. ELISAs were used to quantify ferritin and TfR levels in plasma neuralderived exosomes of patients with PD and controls. Receivers operating characteristic (ROC) curves were applied to map the diagnostic accuracy of ferritin and TfR. The results showed that ferritin and TfR levels in plasma neural-derived exosomes were significantly higher in patients with PD than in controls (406.46±241.86 v.s. 245.62±165.47 ng/µg，P=0.001 and 1728.94 ± 766.71 v.s. 1153.92 ± 539.30 ng/µg ， P<0.001, respectively).. There was also a significant positive correlation between ferritin and TfR levels in plasma neural-derived exosomes in control group, PD group and all the individuals (rs = 0.744, 0.700, and 0.752, respectively). The latter was independently associated with the disease (adjusted odds ratio 1.002; 95%CI 1.000-1.003). ROC performances of ferritin, TfR, and their combination were moderate (0.730 and 0.812, respectively). However, no relationship was found between the biomarkers and disease progression. It is hypothesized that ferritin and TfR in plasma neuralderived exosomes may be potential biomarkers for PD, and that they may participate in the mechanism of excessive iron deposition in PD.